Welding method for aluminum-magnesium dissimilar alloy and application of welding method

By introducing a nickel layer containing nanoparticles in the middle of magnesium alloy and aluminum alloy, and using swing laser welding technology, the problem of hard and brittle phase formation in welding of magnesium alloy and aluminum alloy is solved, and high-quality welding and excellent mechanical properties of joints are achieved.

CN119794569AActive Publication Date: 2025-04-11CHINA-UKRAINE INST OF WELDING GUANGDONG ACAD OF SCI

Patent Information

Application Number
CN202510114143.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-11
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

The prior art is prone to form hard and brittle intermetallic compounds when welding magnesium alloys and aluminum alloys, resulting in uneven weld structure and local cracks, affecting the mechanical properties of the joints.

Method used

A nickel layer containing nanoparticles is introduced as an intermediate layer between the magnesium alloy and the aluminum alloy. By forming Mg-Ni and Al-Ni intermetallic compounds with Mg and Al, the formation of hard and brittle Mg-Al compounds is inhibited, and the weld structure is refined by swinging laser welding technology.

Benefits of technology

High-quality overlap welding of magnesium alloy and aluminum alloy is achieved, and an aluminum-magnesium heterogeneous alloy joint with excellent mechanical properties is obtained. The weld structure is more uniform, which improves the strength and crack resistance of the joint.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119794569A_ABST
    Figure CN119794569A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of welding, and discloses an aluminum-magnesium dissimilar alloy welding method and application thereof. The welding method of the aluminum-magnesium dissimilar alloy comprises the following steps that (1) a magnesium alloy layer, a middle layer and an aluminum alloy layer are in lap joint in sequence from top to bottom, and a to-be-welded piece is obtained; the intermediate layer comprises a nickel layer containing nanoparticles; the nanoparticles comprise at least one of metal carbide, metal boride, metal nitride and metal oxide; and (2) welding the lap joint area of the to-be-welded part. The welding method of the aluminum-magnesium dissimilar alloy is simple and easy to implement, the thickness of the middle layer and the content of nano particles can be effectively controlled, the weld joint structure is refined, the joint strength is improved, the strength and plasticity of the weld joint are improved, cracks are restrained, and the welding method has wide application prospects in the fields of aerospace, automobile manufacturing, electronic engineering and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of welding, and in particular to a welding method for aluminum-magnesium dissimilar alloys and application thereof. Background Art

[0002] Magnesium alloys and aluminum alloys have high specific strength and specific stiffness, and relatively low density, and are widely used in the weight reduction design of automotive parts and aircraft. The widespread application of aluminum alloys and magnesium alloys inevitably involves the dissimilar connection of Mg / Al alloys. However, Mg is easily formed during the welding process of Mg / Al alloys. 17 Al 12 Mg 2 Al 3 The presence of these compounds will lead to uneven microstructure and local cracks in the weld of dissimilar alloys, thus seriously affecting the mechanical properties of Mg / Al alloy dissimilar joints. At present, there are two commonly used solutions: (1) using solid phase welding methods, such as stir friction welding, ultrasonic spot welding, magnetic pulse welding, etc. During the solid phase welding process, the metal base material does not melt, the welding temperature is low, and the heat input is small, which can reduce the formation of hard and brittle phases; (2) adding a Ti intermediate layer between the Mg alloy and the Al alloy base material, and introducing the Ti intermediate layer to form new intermetallic compounds with good plasticity with the Mg alloy and the Al alloy, thereby inhibiting the Mg alloy from melting. 17 Al 12 Mg 2 Al 3 Formation of brittle phase.

[0003] However, although solid phase welding technology can reduce the formation of Mg-Al hard and brittle phases to a certain extent, the stirring head of the friction stir welding is difficult to adapt to workpieces with complex shapes or irregular surfaces, resulting in reduced welding quality or inability to complete welding; at the same time, the stirring head of the friction stir welding cannot enter smoothly in occasions with narrow welding space, further limiting its application. Secondly, although the introduction of the Ti intermediate layer inhibits the formation of Al-Mg intermetallic compounds and improves the strength of the dissimilar joints, a complete Al-Ti compound layer is still formed in the weld, resulting in limited overall improvement in joint strength.

[0004] Therefore, it is urgent to develop a more efficient and flexible welding method for aluminum-magnesium dissimilar alloys that can inhibit the formation of brittle intermetallic compounds while improving the joint strength. This is of great significance to promoting the application and development of Mg alloys and Al alloys in a wider range of fields. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a welding method for aluminum-magnesium dissimilar alloys and its application.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] In a first aspect, the present invention provides a method for welding aluminum-magnesium dissimilar alloys, comprising the following steps:

[0008] (1) overlapping a magnesium alloy layer, an intermediate layer and an aluminum alloy layer in order from top to bottom to obtain a welded part; the intermediate layer comprises a nickel layer containing nanoparticles; the nanoparticles comprise at least one of metal carbides, metal borides, metal nitrides and metal oxides;

[0009] (2) Welding is performed on the overlapping areas of the workpieces to be welded.

[0010] The welding method of aluminum-magnesium dissimilar alloys of the present invention introduces a special intermediate layer between the magnesium alloy and the aluminum alloy, realizes high-quality lap welding of the magnesium alloy and the aluminum alloy, and obtains an aluminum-magnesium dissimilar alloy welded joint with excellent mechanical properties. The Ni layer introduced in the intermediate layer of the present invention can inhibit the formation of hard and brittle Mg-Al compounds by forming Mg-Ni and Al-Ni intermetallic compounds with Mg and Al; at the same time, the uniformly dispersed nanoparticles in the Ni layer can effectively enter the Mg-rich and Al-rich welds during the welding process, on the one hand, improving the uniformity of the weld, and on the other hand, refining the size of the matrix grains and the Mg-Ni, Al-Ni, Mg-Al intermetallic compounds in the weld, making the weld structure more uniform, and effectively reducing the degree of stress concentration near the compound. At the same time, the uniformity and refinement of the weld structure further synergistically improve the strength of the dissimilar joint, so that the aluminum-magnesium dissimilar alloy has excellent mechanical properties.

[0011] As a preferred embodiment of the welding method of aluminum-magnesium dissimilar alloys of the present invention, the metal carbide is titanium carbide; the metal boride is titanium diboride; the metal nitride is aluminum nitride; and the metal oxide is aluminum oxide.

[0012] As a preferred embodiment of the welding method of aluminum-magnesium dissimilar alloys of the present invention, the thickness of the intermediate layer is 50μm-200μm; the diameter of the nanoparticles is 30nm-500nm; the mass of the nanoparticles is 3%-7% of the mass of the nickel layer.

[0013] If the thickness of the intermediate layer in the aluminum-magnesium dissimilar alloy of the present invention is too low, the inhibitory effect of the nickel layer containing nanoparticles on the Al-Mg reaction is insufficient, resulting in the formation of a large amount of coarse Al-Mg intermetallic compounds. If the thickness of the intermediate layer is too high, the melting of the nickel layer containing nanoparticles requires a large power, which will cause violent volatilization of the Mg element.

[0014] Preferably, the thickness of the intermediate layer is any one of 50 μm, 100 μm, 150 μm, 200 μm, or a range value between two of them; the diameter of the nanoparticles is any one of 30 nm, 60 nm, 90 nm, 120 nm, 200 nm, 250 nm, 300 nm, 400 nm, 500 nm, or a range value between two of them.

[0015] As a preferred embodiment of the welding method of aluminum-magnesium dissimilar alloys of the present invention, the intermediate layer further includes an aluminum substrate.

[0016] Preferably, the thickness of the aluminum substrate is 50 μm-80 μm.

[0017] As a preferred embodiment of the aluminum-magnesium dissimilar alloy welding method of the present invention, the intermediate layer is made of electroplated nickel and the nanoparticles on an aluminum substrate.

[0018] The intermediate layer of the present invention is obtained by electroplating Ni and nanoparticles on an aluminum substrate by a composite electroplating method. The preparation method of the intermediate layer of the present invention is simple and easy, does not require complicated equipment and processes, can effectively control the thickness of the intermediate layer and the content of nanoparticles, refine the weld structure, improve the joint strength, and make the nanoparticles dispersed evenly, which further helps to reduce the agglomeration phenomenon between particles, thereby reducing the risk of stress concentration and hindering the expansion path of cracks, and improving the crack resistance of the weld.

[0019] Preferably, the electroplating solution used in the electroplating includes nickel sulfate with a concentration of 240g / L-310g / L, nickel chloride with a concentration of 40g / L-60g / L, boric acid with a concentration of 30g / L-45g / L, and nanoparticles with a concentration of 5g / L-40g / L; the current density of the electroplating is 30mA / cm 2 -80mA / cm 2 ; The electroplating time is 10min-60min.

[0020] Further preferably, the concentration of nickel sulfate is 280 g / L; the concentration of nickel chloride is 40 g / L; the concentration of boric acid is 40 g / L; the concentration of the nanoparticles is 5 g / L, 8 g / L, 9 g / L, 10 g / L, 12 g / L, 15 g / L, 18 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, any one of them or a range value between two of them.

[0021] Further preferably, the current density of the electroplating is 30 mA / cm 2 , 40mA / cm 2 , 50mA / cm 2 、60mA / cm 2 , 70mA / cm2 、80mA / cm 2 The electroplating time is any one of 10min, 20min, 30min, 40min, 50min, 60min or a range value between them.

[0022] As a preferred embodiment of the welding method of aluminum-magnesium dissimilar alloys of the present invention, the welding is oscillating laser welding.

[0023] The welding method of aluminum-magnesium dissimilar alloys of the present invention uses a swing laser welding technique to weld the overlapping area of ​​magnesium alloy-intermediate layer-aluminum alloy (see the specific welding process for details). Figure 1 and Figure 2 ) for lap welding, successfully achieved high-quality lap welding of magnesium alloy and aluminum alloy, and obtained aluminum-magnesium dissimilar alloy joints with excellent mechanical properties. The Ni layer introduced in the intermediate layer of the present invention can inhibit the formation of hard and brittle Mg-Al compounds by forming Mg-Ni and Al-Ni intermetallic compounds with Mg and Al; at the same time, the uniformly dispersed nanoparticles in the Ni layer can effectively enter the Mg-rich and Al-rich welds during the welding process under the influence of the swinging laser, and through the swinging of the laser beam, the weld can be precisely controlled, the uniformity of the weld is improved, and the uniform distribution of nanoparticles in the weld is promoted, which greatly refines the size of the matrix grains and Mg-Ni, Al-Ni, Mg-Al intermetallic compounds in the weld, making the weld structure more uniform, and effectively reducing the degree of stress concentration near the compound. In addition, the uniformity and refinement of the weld structure further synergistically improve the strength of the dissimilar joint, so that the aluminum-magnesium dissimilar alloy obtained by the preparation method has excellent mechanical properties.

[0024] Preferably, the frequency of the oscillating laser welding is 50Hz-600Hz; the oscillation amplitude of the oscillating laser welding is 0.5mm-5mm; the oscillating laser trajectory of the oscillating laser welding is any one of linear, spiral, circular, sinusoidal, "8"-shaped, and "∞"-shaped.

[0025] Further preferably, the frequency of the oscillating laser welding is any one of 50 Hz, 100 Hz, 200 Hz, 300 Hz, 400 Hz, 500 Hz, 600 Hz or a range value between two of them; the oscillation amplitude of the oscillating laser welding is any one of 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm or a range value between two of them.

[0026] Preferably, the power of the swing laser welding is 500W-2500W; the welding speed of the swing laser welding is 30mm / s-100mm / s; argon protection is adopted during the swing laser welding process; the gas flow rate of the argon gas is 5L / min-25L / min, and the defocus amount of the swing laser welding is -3mm-0mm.

[0027] Further preferably, the power of the swing laser welding is any one of 500W, 1000W, 1500W, 2000W, 2500W or a range value between them; the welding speed of the swing laser welding is any one of 30mm / s, 40mm / s, 50mm / s, 60mm / s, 70mm / s, 80mm / s, 90mm / s, 100mm / s or a range value between them; the gas flow rate of the argon gas is any one of 5L / min, 10L / min, 15L / min, 20L / min, 25L / min or a range value between them, and the defocus amount of the swing laser welding is any one of -3mm, -2mm, -1mm, 0mm or a range value between them.

[0028] In a second aspect, the present invention provides an aluminum-magnesium dissimilar alloy produced by the welding method.

[0029] The aluminum-magnesium dissimilar alloy prepared by the preparation method of the present invention has a uniform weld structure, which further improves the strength and durability of the joint.

[0030] In a third aspect, the present invention provides the use of the aluminum-magnesium dissimilar alloy in the preparation of aerospace devices, automobile parts, and electronic equipment.

[0031] The aluminum-magnesium dissimilar alloy of the present invention has the characteristics of light weight, high strength, corrosion resistance, good processing performance and welding performance, which makes it have broad application prospects in the fields of aerospace, automobile manufacturing, electronic engineering, etc., such as being able to be used to prepare key components such as structural parts and shells of aerospace vehicles, key components such as automobile body structural parts, engine parts, chassis parts, and electronic equipment housings, heat sinks and other parts, meeting the diverse needs of multiple fields.

[0032] Compared with the prior art, the beneficial effects of the present invention are as follows: first, the welding method of the aluminum-magnesium dissimilar alloy of the present invention introduces a special intermediate layer in the overlapping area of ​​the magnesium alloy and the aluminum alloy, so as to realize high-quality overlapping welding of the magnesium alloy and the aluminum alloy, and the preparation process is simple and easy, does not require complicated equipment and processes, can effectively control the thickness of the intermediate layer and the content of nanoparticles, refine the weld structure, improve the joint strength, and make the nanoparticles dispersed evenly, which further helps to reduce the agglomeration phenomenon between particles, thereby reducing the risk of stress concentration and hindering the expansion path of cracks, and improving the crack resistance of the weld. Secondly, the aluminum-magnesium dissimilar alloy prepared by the present invention combines the lightness of aluminum and the high strength of magnesium at the same time, forming a composite material with excellent mechanical properties, and its weld structure is uniform, which further improves the strength and durability of the joint. In addition, the aluminum-magnesium dissimilar alloy prepared by the present invention has broad application prospects in the fields of aerospace, automobile manufacturing, electronic engineering, etc. due to its characteristics of light weight, high strength, corrosion resistance, good processing performance and welding performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Schematic diagram of the welding process of aluminum-magnesium dissimilar alloys of the present invention;

[0034] Figure 2 It is a schematic diagram of the overlapping area of ​​the aluminum-magnesium dissimilar alloy of the present invention;

[0035] Figure 3 It is a schematic diagram of obtaining a tensile specimen by a wire cutting method according to the present invention. DETAILED DESCRIPTION

[0036] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0037] The following is an elaboration in conjunction with specific embodiments to illustrate the practical effects of the solutions of the present invention.

[0038] Unless otherwise specified, the experimental methods used in the examples are all conventional methods; the materials, reagents, equipment, etc. used, unless otherwise specified, can be obtained from commercial sources.

[0039] The magnesium alloy plate of the following embodiments and comparative examples is 2 mm thick AZ31 magnesium alloy, and the aluminum alloy plate is 2 mm thick 6061-T6 aluminum alloy. The sizes of the magnesium alloy plate and the aluminum alloy plate are both 80 mm*50 mm*2 mm.

[0040] Example 1: Preparation of aluminum-magnesium dissimilar alloys

[0041] (1) Prepare the plating solution: The composition of the plating solution is as follows: 280 g / L nickel sulfate, 40 g / L nickel chloride, 40 g / L boric acid, 10 g / L nanoparticles, the nanoparticles are TiC, and their diameter is 50 nm; the size of the plating tank is 150 mm*100 mm*80 mm, the liquid level is 60 mm, the plating solution volume is 900 ml, and the plating solution solvent is deionized water.

[0042] (2) Preparation of the intermediate layer: The electroplating solution containing TiC nanoparticles in step (1) was subjected to ultrasonic treatment for 45 min. After the ultrasonic treatment, electroplating was started. During the electroplating process, the cathode was an 80 μm thick aluminum foil with a size of 50 mm*10 mm*0.08 mm; the anode was a nickel plate; the current density was 70 mA / cm 2 The electroplating time is 30 min. During the electroplating process, the electromagnetic stirring speed is 300 rpm. After the electroplating, the thickness of the nickel layer containing nanoparticles is 40 μm, and the mass fraction of the nanoparticles in the nickel layer containing nanoparticles is 5.5%.

[0043] (3) Pre-welding treatment: Before welding, the surface of the magnesium alloy plate and the aluminum alloy plate shall be mechanically polished and wiped with acetone or alcohol to thoroughly remove surface oil and other impurities to avoid affecting the welding process.

[0044] (4) Laser oscillating welding: overlap the 80 mm edge of the magnesium alloy plate to be welded and the 80 mm edge of the aluminum alloy plate (such as Figure 1 As shown), in the overlap area (as Figure 2 The intermediate layer prepared in step (2) is clamped and the overlap width is 10mm. During welding, welding is performed along the 50mm side of the workpiece to be welded. The total length of the weld is 50mm. During the welding process, the magnesium alloy plate is placed above the aluminum alloy plate, and the intermediate layer containing nanoparticles is placed between the magnesium alloy plate and the aluminum alloy plate. The thickness of the magnesium alloy plate and the aluminum alloy plate to be welded is 2mm, and the total thickness of the intermediate layer containing nanoparticles is 120μm. The welding method is swing laser welding. The laser used for swing laser welding is a TRUMPF Trupmf Trudisk 10002 laser, the fiber core diameter is 400μm, and the laser spot diameter is 0.6mm. The welding power is 1500W, the welding speed is 50mm / s, the defocus is -1mm, the swing laser frequency is 500Hz, and the swing amplitude is 2mm. Argon gas is used for protection during welding, and the shielding gas flow rate is 15L / min.

[0045] The prepared aluminum-magnesium dissimilar alloy joint was cut by wire to obtain a tensile specimen with a length of 120 mm and a width of 30 mm (the length of the tensile specimen was taken along the length of the aluminum-magnesium dissimilar alloy of 150 mm, and the width of the tensile specimen was taken along the weld) (the schematic diagram of the tensile specimen obtained by wire cutting is shown in Figure 3As shown), at room temperature, a tensile shear test was carried out on the tensile specimen using an MTS55105 universal testing machine with a tensile rate of 0.5 mm / min, and the shear strength of the joint of the aluminum-magnesium dissimilar alloy was measured to be 130 MPa.

[0046] Example 2: Preparation of aluminum-magnesium dissimilar alloys

[0047] (1) Prepare the plating solution: The composition of the plating solution is as follows: 280 g / L nickel sulfate, 40 g / L nickel chloride, 40 g / L boric acid, 10 g / L nanoparticles, the nanoparticles are TiB 2 , its diameter is 30nm; the plating tank size is 150mm*100mm*80mm, the liquid level height is 60mm, the plating solution volume is 900ml, and the plating solution solvent is deionized water.

[0048] (2) Preparation of an intermediate layer containing nanoparticles: The electroplating solution containing TiC nanoparticles in step (1) was subjected to ultrasonic treatment for 45 min. After the ultrasonic treatment, electroplating was started. During the electroplating process, the cathode was a 50 μm thick aluminum foil with a size of 50 mm*10 mm*0.05 mm; the anode was a nickel plate; the current density was 40 mA / cm 2 The electroplating time is 30 min. During the electroplating process, the speed of electromagnetic stirring is 300 rpm. After the electroplating, the thickness of the nickel layer containing nanoparticles is 25 μm, and the mass fraction of the nanoparticles in the nickel layer containing nanoparticles is 3.4%.

[0049] (3) Pre-welding treatment: Before welding, the surface of the magnesium alloy plate and the aluminum alloy plate shall be mechanically polished and wiped with acetone or alcohol to thoroughly remove surface oil and other impurities to avoid affecting the welding process.

[0050] (4) Laser oscillating welding: overlap the 80 mm edge of the magnesium alloy plate to be welded and the 80 mm edge of the aluminum alloy plate (such as Figure 1 As shown), in the overlap area (as Figure 2The intermediate layer prepared in step (2) is clamped and the overlap width is 10mm. During welding, welding is performed along the 50mm side of the workpiece to be welded. The total length of the weld is 50mm. During welding, the magnesium alloy plate is placed above the aluminum alloy plate, and the intermediate layer containing nanoparticles is placed between the magnesium alloy plate and the aluminum alloy plate. The thickness of the magnesium alloy plate and the aluminum alloy plate to be welded is 2mm, and the total thickness of the intermediate layer containing nanoparticles is 75μm. The welding method is swing laser welding. The laser used for swing laser welding is a TRUMPF Trupmf Trudisk 10002 laser, the fiber core diameter is 400μm, and the laser spot diameter is 0.6mm. The welding power is 1500W, the welding speed is 50mm / s, the defocus is -1mm, the swing laser frequency is 500Hz, and the swing amplitude is 2mm. Argon gas is used for protection during welding, and the shielding gas flow rate is 15L / min.

[0051] The prepared aluminum-magnesium dissimilar alloy joint was cut by wire to obtain a tensile specimen with a length of 120 mm and a width of 30 mm (the length of the tensile specimen was taken along the length of the aluminum-magnesium dissimilar alloy of 150 mm, and the width of the tensile specimen was taken along the weld) (the schematic diagram of the tensile specimen obtained by wire cutting is shown in Figure 3 As shown), at room temperature, a tensile shear test was carried out on the tensile specimen using an MTS55105 universal testing machine with a tensile rate of 0.5 mm / min, and the shear strength of the joint of the aluminum-magnesium dissimilar alloy was measured to be 115 MPa.

[0052] Example 3: Preparation of aluminum-magnesium dissimilar alloys

[0053] The only difference between the preparation method of the aluminum-magnesium dissimilar alloy described in this embodiment and that in Embodiment 1 is that in step (1), the nanoparticles are TiC with a diameter of 30 nm, and the joint shear strength of the obtained aluminum-magnesium dissimilar alloy is 140 MPa.

[0054] Example 4: Preparation of aluminum-magnesium dissimilar alloys

[0055] The only difference between the preparation method of the aluminum-magnesium dissimilar alloy described in this embodiment and that in Embodiment 1 is that in step (1), the nanoparticles are TiC with a diameter of 100 nm, and the joint shear strength of the obtained aluminum-magnesium dissimilar alloy is 120 MPa.

[0056] Example 5: Preparation of aluminum-magnesium dissimilar alloys

[0057] The only difference between the preparation method of the aluminum-magnesium dissimilar alloy described in this embodiment and that in Embodiment 1 is that in step (1), the nanoparticles are TiC with a diameter of 500 nm, and the joint shear strength of the obtained aluminum-magnesium dissimilar alloy is 110 MPa.

[0058] Example 6: Preparation of aluminum-magnesium dissimilar alloys

[0059] The only difference between the preparation method of aluminum-magnesium dissimilar alloy described in this embodiment and that in embodiment 1 is that in step (2), the current density is 30 mA / cm 2 After electroplating, the thickness of the nickel layer containing nanoparticles is 23 μm, the mass fraction of nanoparticles in the nickel layer containing nanoparticles is 3.2%, and the shear strength of the joint of the obtained aluminum-magnesium dissimilar alloy is 110 MPa.

[0060] Example 7: Preparation of aluminum-magnesium dissimilar alloys

[0061] The only difference between the preparation method of aluminum-magnesium dissimilar alloy described in this embodiment and that in embodiment 1 is that in step (2), the current density is 80 mA / cm 2 After electroplating, the thickness of the nickel layer containing nanoparticles is 42 μm, the mass fraction of the nanoparticles in the nickel layer containing nanoparticles is 6.0%, and the shear strength of the joint of the obtained aluminum-magnesium dissimilar alloy is 140 MPa.

[0062] Example 8: Preparation of aluminum-magnesium dissimilar alloys

[0063] The only difference between the preparation method of the aluminum-magnesium dissimilar alloy described in this embodiment and that in Embodiment 1 is that in step (2), the concentration of the nanoparticles is 5 g / L, the thickness of the nickel layer containing the nanoparticles after electroplating is 45 μm, the mass fraction of the nanoparticles in the nickel layer containing the nanoparticles is 3.0%, and the joint shear strength of the obtained aluminum-magnesium dissimilar alloy is 105 MPa.

[0064] Example 9: Preparation of aluminum-magnesium dissimilar alloys

[0065] The only difference between the preparation method of the aluminum-magnesium dissimilar alloy described in this embodiment and that in Embodiment 1 is that in step (2), the concentration of the nanoparticles is 20 g / L, the thickness of the nickel layer containing the nanoparticles after electroplating is 35 μm, the mass fraction of the nanoparticles in the nickel layer containing the nanoparticles is 6.5%, and the joint shear strength of the obtained aluminum-magnesium dissimilar alloy is 145 MPa.

[0066] Comparative Example 1: Preparation of aluminum-magnesium dissimilar alloys

[0067] (1) Pre-welding treatment: Before welding, the surface of the magnesium alloy plate and the aluminum alloy plate shall be mechanically polished and wiped with acetone or alcohol to thoroughly remove surface oil and other impurities to avoid affecting the welding process.

[0068] (2) Swinging laser welding: overlap the 80mm side of the magnesium alloy plate to be welded and the 80mm side of the aluminum alloy plate, sandwich a pure nickel intermediate layer in the overlapping area, the overlap width is 10mm, and welding is performed along the 50mm side of the welded parts. The total length of the weld is 50mm. During the welding process, the magnesium alloy plate is placed above the aluminum alloy plate, and the pure nickel intermediate layer is placed between the magnesium alloy plate and the aluminum alloy plate. The thickness of the magnesium alloy plate and the aluminum alloy plate to be welded is 2mm, the thickness of the pure nickel intermediate layer is 120μm, and the welding method is swinging laser welding. The laser used for swinging laser welding is a TRUMPF Trupmf Trudisk 10002 laser, the fiber core diameter is 400μm, and the laser spot diameter is 0.6mm. The welding power is 1500W, the welding speed is 50mm / s, the defocus is -1mm, the swing laser frequency is 500Hz, and the swing amplitude is 2mm. Argon gas is used for protection during welding, and the protective gas flow rate is 15L / min.

[0069] The prepared aluminum-magnesium dissimilar alloy joint was cut by wire to obtain a tensile specimen with a length of 120 mm and a width of 30 mm (the length of the tensile specimen was taken along the length of the aluminum-magnesium dissimilar alloy of 150 mm, and the width of the tensile specimen was taken along the weld) (the schematic diagram of the tensile specimen obtained by wire cutting is shown in Figure 3 As shown), at room temperature, a tensile shear test was carried out on the tensile specimen using an MTS55105 universal testing machine with a tensile rate of 0.5 mm / min, and the shear strength of the joint of the aluminum-magnesium dissimilar alloy was measured to be 80 MPa.

[0070] Comparative Example 2: Preparation of aluminum-magnesium dissimilar alloys

[0071] (1) Prepare the plating solution: The composition of the plating solution is as follows: 280 g / L nickel sulfate, 40 g / L nickel chloride, 40 g / L boric acid, 10 g / L nanoparticles, the nanoparticles are TiC, and their diameter is 50 nm; the size of the plating tank is 150 mm*100 mm*80 mm, the liquid level is 60 mm, the plating solution volume is 900 ml, and the plating solution solvent is deionized water.

[0072] (2) Preparation of the intermediate layer: The electroplating solution containing TiC nanoparticles in step (1) was subjected to ultrasonic treatment for 45 min. After the ultrasonic treatment, electroplating was started. During the electroplating process, the cathode was an 80 μm thick aluminum foil with a size of 50 mm*10 mm*0.08 mm; the anode was a nickel plate; the current density was 70 mA / cm 2 The electroplating time is 30 min. During the electroplating process, the electromagnetic stirring speed is 300 rpm. After the electroplating, the thickness of the intermediate layer containing nanoparticles is 40 μm, and the mass fraction of nanoparticles in the intermediate layer is 5.5%.

[0073] (3) Pre-welding treatment: Before welding, clean the surface of magnesium alloy plate and aluminum alloy plate to thoroughly remove surface oil and other impurities to avoid affecting the welding process.

[0074] (4) Laser welding: overlap the 80 mm side of the magnesium alloy plate to be welded and the 80 mm side of the aluminum alloy plate, and sandwich the intermediate layer prepared in step (2) in the overlap area. The overlap width is 10 mm. During welding, welding is performed along the 50 mm side of the welded parts. The total length of the weld is 50 mm. During the welding process, the magnesium alloy plate is placed above the aluminum alloy plate, and the intermediate layer containing nanoparticles is placed between the magnesium alloy plate and the aluminum alloy plate. The thickness of the magnesium alloy plate and the aluminum alloy plate to be welded is 2 mm, the total thickness of the intermediate layer is 120 μm, and the welding method is laser welding. The laser used for laser welding is a TRUMPF Trudisk 10002 laser, the fiber core diameter is 400 μm, and the laser spot diameter is 0.6 mm. The welding power is 1500 W, the welding speed is 50 mm / s, the defocus is -1 mm, and the laser does not swing during the welding process. Argon gas is used for protection during the welding process, and the protective gas flow rate is 15 L / min.

[0075] The prepared aluminum-magnesium dissimilar alloy joint was cut by wire cutting to obtain a tensile specimen with a length of 120 mm and a width of 30 mm (the length of the tensile specimen was cut along the length of the aluminum-magnesium dissimilar alloy at 150 mm, and the width of the tensile specimen was cut along the weld) (the schematic diagram of the tensile specimen obtained by wire cutting is shown in FIG. Figure 3 As shown), at room temperature, a tensile shear test was carried out on the tensile specimen using an MTS55105 universal testing machine with a tensile rate of 0.5 mm / min, and the shear strength of the joint of the aluminum-magnesium dissimilar alloy was measured to be 110 MPa.

[0076] Comparative Example 3: Preparation of aluminum-magnesium dissimilar alloys

[0077] The only difference between the preparation method of the aluminum-magnesium dissimilar alloy described in this comparative example and that of Example 1 is that in step (1), the nanoparticles are TiC with a diameter of 10 nm, and the joint shear strength of the obtained aluminum-magnesium dissimilar alloy is 95 MPa.

[0078] Comparative Example 4: Preparation of aluminum-magnesium dissimilar alloys

[0079] The only difference between the preparation method of the aluminum-magnesium dissimilar alloy described in this comparative example and that of Example 1 is that in step (1), the nanoparticles are TiC with a diameter of 600 nm, and the joint shear strength of the obtained aluminum-magnesium dissimilar alloy is 115 MPa.

[0080] Comparative Example 5: Preparation of aluminum-magnesium dissimilar alloys

[0081] The only difference between the preparation method of the aluminum-magnesium dissimilar alloy described in this comparative example and that of Example 1 is that in step (2), the concentration of the nanoparticles is 3 g / L, the thickness of the nickel layer containing the nanoparticles after electroplating is 43 μm, the mass fraction of the nanoparticles in the nickel layer containing the nanoparticles is 2%, and the joint shear strength of the obtained aluminum-magnesium dissimilar alloy is 100 MPa.

[0082] Comparative Example 6: Preparation of aluminum-magnesium dissimilar alloys

[0083] The only difference between the preparation method of the aluminum-magnesium dissimilar alloy described in this comparative example and that of Example 1 is that in step (2), the concentration of the nanoparticles is 50 g / L, the thickness of the nickel layer containing the nanoparticles after electroplating is 30 μm, the mass fraction of the nanoparticles in the nickel layer containing the nanoparticles is 5%, and the joint shear strength of the obtained aluminum-magnesium dissimilar alloy is 105 MPa.

[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for welding aluminum-magnesium dissimilar alloys, characterized in that: The following steps are involved: (1) overlapping a magnesium alloy layer, an intermediate layer and an aluminum alloy layer in order from top to bottom to obtain a welded part; the intermediate layer comprises a nickel layer containing nanoparticles; the nanoparticles comprise at least one of metal carbides, metal borides, metal nitrides and metal oxides; (2) Welding is performed on the overlapping areas of the workpieces to be welded.

2. The method for welding aluminum-magnesium dissimilar alloys according to claim 1, characterized in that: The metal carbide is titanium carbide; the metal boride is titanium diboride; the metal nitride is aluminum nitride; and the metal oxide is aluminum oxide.

3. The method for welding aluminum-magnesium dissimilar alloys according to claim 1, characterized in that: The thickness of the intermediate layer is 50 μm-200 μm.

4. The method for welding aluminum-magnesium dissimilar alloys according to claim 1, characterized in that: The diameter of the nanoparticles is 30nm-500nm; the mass of the nanoparticles is 3%-7% of the mass of the nickel layer.

5. The method for welding aluminum-magnesium dissimilar alloys according to claim 1, characterized in that: The intermediate layer is made of electroplated nickel and the nanoparticles on an aluminum substrate.

6. The method for welding aluminum-magnesium dissimilar alloys according to claim 5, characterized in that: The electroplating solution used in the electroplating includes nickel sulfate with a concentration of 240g / L-310g / L, nickel chloride with a concentration of 40g / L-60g / L, boric acid with a concentration of 30g / L-45g / L, and nanoparticles with a concentration of 5g / L-40g / L; the current density of the electroplating is 30mA / cm 2 -80mA / cm 2 ; The electroplating time is 10min-60min.

7. The method for welding aluminum-magnesium dissimilar alloys according to claim 1, characterized in that: The welding is oscillating laser welding.

8. The method for welding aluminum-magnesium dissimilar alloys according to claim 7, characterized in that: The frequency of the oscillating laser welding is 50Hz-600Hz; the oscillation amplitude of the oscillating laser welding is 0.5mm-5mm; the oscillating laser trajectory of the oscillating laser welding is any one of a linear, spiral, circular, sinusoidal, "8" shape, and "∞" shape.

9. Aluminum-magnesium dissimilar alloy obtained by the welding method according to any one of claims 1 to 8.

10. Use of the aluminum-magnesium dissimilar alloy according to claim 9 in the preparation of aerospace devices, automobile parts, and electronic equipment.

Citation Information

Patent Citations

  • Spreading welding method of magnesium alloy and aluminum alloy containing composite middle layer

    CN102861986A

  • Laser filler welding process of magnesium / aluminum dissimilar metal

    CN108526692A

  • Method for producing welded joint by laser arc hybrid welding

    CN116438035A

  • Brazing method for magnesium / aluminum dissimilar metal

    CN116652314A

  • Composite welding method for improving mechanical property of high-strength aluminum alloy welded joint

    CN118305446A

Cited By

  • Laser cutting machining method for copper-aluminum connector

    CN121061388A